Legitimizing a New Role: Small Wins and Microprocesses of Change - Reay, Trish; Golden-Biddle, Karen; Germann, Kathy (Academy of Management Journal, 2006)
How do individual actors institute changes in established ways of working? Longitudinal research is the basis for our theoretical model showing how actors legitimize new practices by accomplishing three interdependent, recursive, situated “microprocesses”: (1) cultivating opportunities for change, (2) fitting a new role into prevailing systems, and (3) proving the value of the new role. These microprocesses are demarcated by an accumulating series of small wins that consolidate gains while facilitating continuing change efforts. Most accounts of institutional change focus on embeddedness as a constraint, yet our study shows how embeddedness can provide the foundation and opportunity for change.